Pengaruh Stres Kerja Dan Lingkungan Kerja Terhadap Kinerja Karyawan Pada PT.Pegadaian (Persero) Cab. BSD City - Rohima Nurhayati; Muger Apriyansyah (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This study aims to analyze the effect of work stress and work environment on employee performance at PT Pegadaian (Persero) BSD City Branch. The research is motivated by the importance of employee performance in maintaining service quality and operational effectiveness within the company. This study employs a quantitative approach with 85 respondents selected using a census technique. Data were collected through questionnaires and analyzed using validity tests, reliability tests, multiple linear regression, t-tests, F-tests, and the coefficient of determination, assisted by SPSS version 25. The results show that work stress has a positive and significant effect on employee performance, with a regression coefficient of 0.235 and a significance value of <0.005. The work environment also has a positive and significant effect on employee performance, with a regression coefficient of 0.377 and a significance value of 0.000. Simultaneously, work stress and work environment significantly influence employee performance, as shown by the R Square value of 0.533. This indicates that both variables explain 53.3% of the variation in employee performance, while the remaining 46.7% is influenced by other factors beyond the scope of this study. This study concludes that managing work stress and creating a conducive work environment play an important role in improving employee performance at PT Pegadaian (Persero) BSD City Branch.